Refugee status as a bar to extradition? A comparative perspective on Russian and Belarusian law - Soltanowich, Anna A.; Kruessmann, Thomas (Journal of the Belarusian State University. Law, 2019)
Neither Russia nor Belarus have been significantly touched by the current wave of refugee flows stemming from the Near and Middle East as well as from Northern Africa. Recently though, their systems of refugee protection have been used by fugitives from other Eurasian Economic Union countries, primarily from Kazakhstan, to claim refugee status in order to escape extradition requests from their home countries. This article looks into the question how easily refugee status can be obtained in Russia and Belarus and what protections it offers in a comparative perspective. It argues that for Russia (which is the preferred destination), refugee status does not provide a per se bar to extradition, but that a human rights-based non refoulement needs to be observed. Belarusian law, by comparison, is much more amenable. In order to prevent the emergence of safe havens within the Eurasian Economic Union, criminal justice cooperation needs to be modernized.
Keywords: refugee status; extradition; Chisinau Convention; Minsk Convention; non-refoulement